(untitled) (SAARC Journal of Agriculture, 2016)
The behaviour of introgressed male-sterilility with respect to various morphological traits is based on its superior performance in segregating backcross populations. In this study a maiden attempt has been made to identify male sterile lines suitable for developing aerobic rice hybrids. Two BC2F1 populations derived from IR70369A x MAS 99 and KCMS31A x MAS 99 crosses were evaluated for various morpho-floral traits. Pollen and spikelet fertility test revealed that all plants of these populations were completely male sterile. Genetic variability studies indicated high heritability for most of the traits (>60%). Narrow variation between Phenotypic Co-efficient of variation (PCV) and Genotypic Coefficient of Variation (GCV) was observed for most traits. Stigma exertion, Panicle exertion, Tiller number and Spikelet per panicle recorded moderate heritability with wider differenced between PCV and GCV. Negatively skewed platykurtic distribution was observed for most of the traits in both BC2F1 populations. The identified new male sterile lines will be stabilised, and they could serve as potential A lines for development of rice hybrids for aerobic condions. SAARC J. Agri., 13(2): 198-213 (2015)